Proximate Composition of Selected Freshwater Fish from Kampung Peta, Johor, Malaysia - Sa’ari, Naziatul Izzaty; Abu Bakar, Mohd Fadzelly; Malik, Nur Hafizah (Journal of Sustainable Natural Resources, 2021)
Four species of freshwater fish from Kampung Peta, Johor namely Osteochilus flavicauda (Rong batu sirip), Labiobarbus festivus (Kawan), Barbonymus gonionotus (Lampam Jawa) and Puntioplites bulu (Tenggalan) were investigated in this study. The selected freshwater fishes from the Cyprinidae family were analyzed for their physical properties and proximate composition. The fishes exhibited weight of less than 400 g and have body length between 16 to 23 cm. Proximate analysis revealed that all fish species had comparable (p > 0.05) crude protein (13.40 - 13.75%) and ash content (2.76 - 3.27%) with each other. The moisture content was found to be between 77.02-82.65% where B. gonionotus exhibited a significantly (p < 0.05) higher percentage than the other species. The freshwater fishes were identified to be a lean fish containing crude fat of less than 2%. The highest (1.09 %) and lowest (0.48 %) amount of fat were recorded for O. flavicauda and B. gonionotus respectively. Meanwhile, the carbohydrate value ranging from 0.46 % to 5.26 % was inversely related to the protein content. Significant differences in carbohydrate value (p < 0.05) were observed between O. flavicauda (5.26%), L. festiva (2.91 %) and B. gonionotus (0.46%) while L. festiva and P. bulu (3.57%) showed insignificant differences (p > 0.05). These values are useful as a baseline data on the nutritional quality of freshwater fish from Kampung Peta, Johor.